Deployment strategies of on-orbit service vehicles for multi-objective group and multiple spacecraft. (2017) - Zhang, Jianxin; Zhang, Qiang; Wei, Xiaopeng
A novel deployment method of on-orbit service vehicles (OSVs) design for multiple-objective and multiple-orbit missions is evaluated in this paper. The given deployment method mainly includes four steps, and respectively are: 1) dividing the predetermined region into unequal and independent servicing spaces; 2) calculating parking-orbit for different target areas; 3) computing the minimum number of OSVs; 4) calculating the position elements of each parking-orbit. The proposed method can cover the service areas by using the fewest OSVs, which can improve the efficiency of the OSV program. Although the present exploration of deployment strategy is based on circular orbital models, this method can be directly extended to other orbital models. The calculation examples based on Glonass and GPS constellation orbits shows the proposed method is effective.